Analysis of dimensions and elements of customer loyalty in from Sergipe musical event - Andrade, Mariana Melo Carvalho; Muniz, Emerson Cleister Lima (Brazilian Journal of Production Engineering, 2024)
Leisure is part of the population's daily life and entertainment options grow every day, including musical events that have a growing share in the economy. Therefore, this work investigates which elements most influence customer loyalty at musical events. To this end, it identifies, via an integrative systematic review of the literature, 03 main dimensions of loyalty, namely Connection, Satisfaction and Experience and 12 elements belonging to them. They were verified by a survey among customers of a musical event, obtaining 101 valid responses for analysis and verification of theory versus reality. From the results it was found that the Satisfaction dimension has the greatest influence on the sample, highlighting elements such as the quality of cleaning, hygiene and food services, pricing policy practiced, diversification of attractions, among others. While the Connection dimension had less influence. Furthermore, the elements were analyzed by customer profile, bringing a concatenation of opportunities and insights that contribute to improving the experience offered by the event and boosting public loyalty. Finally, this research fills a research gap in Entertainment Engineering, a field that is still little explored on the national scene and with few empirical studies
Keywords: Customer loyalty; Loyalty elements; Loyalty dimensions; Musical Event; Entertainment Engineering